Enhancing E-Commerce for Book Sales: Development and Evaluation of the B-Store Mobile Application - Kurnia Prima Putra (Journal of Embedded Systems, Security and Intelligent Systems, 2024)
The mobile-based online book store application B-Store was developed to enhance the effectiveness and efficiency of book promotion and sales through an e-commerce platform. This research aims to develop effective promotional strategies, identify consumer obstacles in searching and purchasing books online, and design application features that meet consumer needs. By using hardware and software requirements analysis, software design, flowchart diagrams, use case diagrams, and data flow diagrams, the B-Store application successfully meets user needs in purchasing books online. Code implementation was done in Java using Android Studio, and testing was conducted using a Likert scale questionnaire, indicating user satisfaction with the application. The conclusion of this study is that the B-Store application successfully improved services for book sellers and provided a more convenient shopping experience for consumers through an intuitive online book sales platform.